+0  
 
0
57
2
avatar

Solve in real numbers: \(x^2 + 7x - 5 = 5 \sqrt{x^3 - 1}\)

 May 17, 2020
 #1
avatar
-1

 Solve for x:
x^2+7 x-5==5 Sqrt[x^3-1]


x^2+7 x-5==5 Sqrt[x^3-1] is equivalent to 5 Sqrt[x^3-1]==x^2+7 x-5:
5 Sqrt[x^3-1]==x^2+7 x-5


Raise both sides to the power of two:
25 (x^3-1)==(x^2+7 x-5)^2


Expand out terms of the left hand side:
25 x^3-25==(x^2+7 x-5)^2


Expand out terms of the right hand side:
25 x^3-25==x^4+14 x^3+39 x^2-70 x+25


Subtract x^4+14 x^3+39 x^2-70 x+25 from both sides:
-x^4+11 x^3-39 x^2+70 x-50==0


The left hand side factors into a product with three terms:
-(x^2-8 x+10) (x^2-3 x+5)==0


Multiply both sides by -1:
(x^2-8 x+10) (x^2-3 x+5)==0


Split into two equations:
x^2-8 x+10==0 or x^2-3 x+5==0


Subtract 10 from both sides:
x^2-8 x==-10 or x^2-3 x+5==0


Add 16 to both sides:
x^2-8 x+16==6 or x^2-3 x+5==0


Write the left hand side as a square:
(x-4)^2==6 or x^2-3 x+5==0


Take the square root of both sides:
x-4==Sqrt[6] or x-4==-Sqrt[6] or x^2-3 x+5==0


Add 4 to both sides:
x==4+Sqrt[6] or x-4==-Sqrt[6] or x^2-3 x+5==0


Add 4 to both sides:
x==4+Sqrt[6] or x==4-Sqrt[6] or x^2-3 x+5==0


Subtract 5 from both sides:
x==4+Sqrt[6] or x==4-Sqrt[6] or x^2-3 x==-5


Add 9/4 to both sides:
x==4+Sqrt[6] or x==4-Sqrt[6] or x^2-3 x+9/4==-(11/4)


Write the left hand side as a square:
x==4+Sqrt[6] or x==4-Sqrt[6] or (x-3/2)^2==-(11/4)


Take the square root of both sides:
x==4+Sqrt[6] or x==4-Sqrt[6] or x-3/2==(I Sqrt[11])/2 or x-3/2==-((I Sqrt[11])/2)


Add 3/2 to both sides:
x==4+Sqrt[6] or x==4-Sqrt[6] or x==3/2+(I Sqrt[11])/2 or x-3/2==-((I Sqrt[11])/2)


Add 3/2 to both sides:
x==4+Sqrt[6]   or   x==4-Sqrt[6]   or   x==3/2+(I Sqrt[11])/2   or   x==3/2-(I Sqrt[11])/2

 May 17, 2020
 #2
avatar+74 
+2

cheekycoolx =  -(√6) + 4  x = (sqrt6) + 4cheekycool

 May 17, 2020

15 Online Users

avatar
avatar
avatar